Nilai-Nilai Pendidikan dalam Pandangan Al-Quran : Studi atas Kisah Lukman Al-Hakim - Nurmin Junus; Kasim Yahiji; Ilyas Daud; Rahmin T. Husain (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2024)
This paper discusses the educational values of the Quranic stories, especially the story of Lukman al-Hakim. This research looks at the story of Lukman al-Hakim through the views of Muslim figures. This research uses qualitative research with the type of library research. The results of this study are the story of Lukman al-Hakim including creed, sharia and moral education. The education of faith is the placement of monotheism in a person so as not to associate gods, sharia education to uphold the sharia of god, especially carrying out god's commands and keeping away from his prohibitions, and moral education is to strive to do good things and stay away from arrogance.